Keterampilan Bahasa Inggris Mahasiswa Karyawan di Akademi Pariwisata Denpasar - Eka Anastasia Wijaya; Putu Bagus Wisnuwardhana; Ida Bagus Gde Upadana; A.A. Sagung Ayu Srikandi Putri (Jurnal Kajian dan Terapan Pariwisata, 2022)
This research aimed to investigate the student employees' English language skills at Denpasar Academy of Tourism. Framed within a qualitative design, this study employed observation, survey, and interview as the methods with an observation sheet, a questionnaire, and an interview guide as the instruments to collect the data. It is expected that working students have the ability to communicate well in English. However, the results of the study showed that the working students’ English skills are moderate. Therefore, the students need to maximize their English skills to support them in the work field. Further, this study could be used as a reflection to improve the process of English teaching and learning by upgrading the curriculum and creating an English club.